Електронне урядування в органах державної влади - Приставська, Ірина; Ярка, Уляна (Видавництво Львівської політехніки, 2015)
E-government is one of the tools of the Information Society, the implementation of which will contribute to the creation of conditions for open and transparent public administration.
Keywords: електронне урядування; прийняття рішень; управління; суспільство; інфраструктура